Development of iron-based biochar for enhancing nitrate adsorption: Effects of specific surface area, electrostatic force, and functional groups - Zhang, Zhen; Huang, Guohe; Zhang, Peng; Shen, Jian; Wang, Shuguang; Li, Yongping (The Science of the total environment, 2023)
The problem of nitrate contamination in water has attracted widespread attention. Original biochar has a poor adsorption capacity for nitrate adsorption. Iron impregnation and acid protonation (base deprotonation) are common modification methods for biochar. In order to develop iron-mediated biochar containing multi-functional groups for enhancing nitrate adsorption, Fe-BC@H and Fe-BC@OH were prepared using a two-stage development process, including an iron-based carbon pyrolysis followed by acid protonation (or base deprotonation). The pseudo-second-order kinetic and Langmuir models can well describe the adsorption process which is a physicochemical complex monolayer adsorption. The data proved that Fe-BC@H (9.35 mg/g NO3−-N) had a stronger adsorption capacity than Fe-BC@OH (2.95 mg/g NO3−-N). Surface morphologies, functional groups, and mineral compositions of Fe-BC@H and Fe-BC@OH were analyzed through Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). Characterization results showed that acid protonation can further improve the specific surface area (SSA), pore volume, and Zeta potential of Fe-based biochar, providing more adsorption sites for nitrate and enhancing the electrostatic force between nitrate and biochar. However, these effects were suppressed through base deprotonation. In addition, acid protonation can significantly increase the type and number of functional groups of biochar to enhance the chemisorption of nitrate. Such results suggested that the acid protonation can further improve the adsorption capacity of Fe-based biochar for nitrate, while base deprotonation had an inhibitory effect on that of Fe-based biochar. Overall, this study reveals that specific surface area, electrostatic force, and functional groups are crucial effects of the nitrate adsorption on acid/base modified biochar. [Display omitted] •More nitrates were adsorbed on protonated Fe-based biochar than deprotonated one.•Pseudo-second-order kinetic and Langmuir models represented nitrate adsorption.•Protonated Fe-based biochar helped increase in electrostatic force and hydroxyl.•Radius-oriented pore-filling effects dominated competitive adsorption of anions.•Chemical bond formation with phosphate occupied nitrate adsorption sites.